Blogs of their own: a story of two Malaysian Women Bloggers - Ruzy Suliza Hashim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
Over the last few years, with the introduction of easy-to-use and integrated services such as Windows Live Spaces, blogging has moved into the mainstream in Malaysia, with women making up 64% of bloggers. Blogging has become popular because it provides an outlet for netizens who find blogosphere a liberating place, so unlike Malaysian traditional print which is censored and licensed. This article is an analysis of two blogs written by Malaysian women that show them negotiating in contradictory ways the line between the private and public dimensions of their lives. The idea that the “personal is political” and the importance of experience still retain an important place in feminist contemporary thought. I argue that many seemingly “trivial and personal” issues have produced a politics formed from the bloggers‟ personal experiences and reflections.